Faktor-Faktor yang Mempengaruhi Indeks Pembangunan Manusia Melalui Belanja Daerah Sebagai Variabel Pemediasi - Eza Putri Madyansyah; Dwi Suhartini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research uses quantitative techniques to examine and evaluate the impact of the Revenue Sharing Fund and Special Allocation Fund on the Human Development Index using regional expenditure as a mediating variable. The East Nusa Tenggara region's 110 data points from 22 districts and cities between 2019 and 2023 served as the study's sample. Path analysis and multiple linear regression are the study approaches that are employed. The results of this study prove that increasing the amount of Special Allocation Fund (DAK) and Revenue Sharing Fund (DBH) can increase Regional Expenditure, besides that DBH is able to increase the Human Development Index (HDI), DAK and Regional Expenditure have not contributed to changes in HDI, and DAK and DBH have no impact on HDI through Regional Expenditure. This illustrates that the East Nusa Tenggara local government has optimized the allocation of Revenue Sharing Funds through extracting funds by utilizing the potential of natural resources and taxes as a strategy to improve the quality of the Human Development Index through improvements in education, health, and income levels.